Oronasal and Orosinusal Lesions Associated with Intranasal Cocaine Use: Two Clinical Case Reports - Pereira, Cláudio Maranhão; Almeida, Kevin Cavalcante; Lopes, Laura Beatriz Sousa; Lopes, Lara Bianca Sousa; Gasparetto, Patrícia Freire; Andrade, Leonardo Araújo de (Brazilian Journal of Case Reports, 2026)
Intranasal cocaine use may lead to a progressive spectrum of centrofacial destruction known as cocaine-induced midline destructive lesion (CIMDL), which may involve the hard palate and result in oronasal or orosinusal communication, with major functional and social repercussions. Because oral examination routinely exposes the palate, dentists may be the first clinicians to detect these lesions; however, diagnosis is often delayed because patients may initially omit illicit drug use and because the clinical presentation may overlap with vasculitic, infectious, and neoplastic disorders. This report describes two cases of cocaine-associated palatal destruction diagnosed at different stages of progression and discusses the main etiopathogenic, histopathological, diagnostic, and therapeutic aspects relevant to dental practice. The first case involved a woman with an established palatal perforation measuring approximately 3 cm, hypernasal speech, nasal regurgitation of food and liquids, and improvised self-occlusion of the defect with plastic material. The second case involved a 35-year-old man with a posterior palatal nodule, computed tomographic evidence of osteolysis affecting the floor of the nasal cavity, and incisional biopsy showing chronic granulomatous inflammation in the context of chronic intranasal cocaine use. Together, these cases illustrate that cocaine-related palatal destruction may be identified at markedly different points along the same pathological continuum, from pre-perforative osteolytic disease to extensive communication with severe functional impairment. Early recognition, structured differential diagnosis, cocaine cessation, and multidisciplinary rehabilitation are essential for appropriate management.